Mitochondria modify exercise-induced development of stem cell-derived neurons in the adult brain - Steib, Kathrin; Schäffner, Iris; Jagasia, Ravi; Ebert, Birgit; Lie, Dieter Chichung (The Journal of Neuroscience, 2014)
Neural stem cells in the adult mammalian hippocampus continuously generate new functional neurons, which modify the hippocampal network and significantly contribute to cognitive processes and mood regulation. Here, we show that the development of new neurons from stem cells in adult mice is paralleled by extensive changes to mitochondrial mass, distribution, and shape. Moreover, exercise-a strong modifier of adult hippocampal neurogenesis-accelerates neuronal maturation and induces a profound increase in mitochondrial content and the presence of mitochondria in dendritic segments. Genetic inhibition of the activity of the mitochondrial fission factor dynamin-related protein 1 (Drp1) inhibits neurogenesis under basal and exercise conditions. Conversely, enhanced Drp1 activity furthers exercise-induced acceleration of neuronal maturation. Collectively, these results indicate that adult hippocampal neurogenesis requires adaptation of the mitochondrial compartment and suggest that mitochondria are targets for enhancing neurogenesis-dependent hippocampal plasticity.
EVALuna2:26325